2018
DOI: 10.3390/nu10121886
|View full text |Cite
|
Sign up to set email alerts
|

Green Tea Consumption and Risk of Breast Cancer and Recurrence—A Systematic Review and Meta-Analysis of Observational Studies

Abstract: Breast cancer (BC) is the most common cancer in women and several factors are involved in its onset. Green tea (GT) has been shown to have potential beneficial effects on different types of cancer. The aim of this review was to evaluate the association between GT regular consumption and risk of BC in women. The risk of BC recurrence and risk of BC in relation to menopausal status were also evaluated. A literature search of PubMed, Scopus, and Web of Science was conducted. Preferred Reporting Items for Systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 76 publications
0
35
0
Order By: Relevance
“…The significance of case-control studies in defining the causal relationship between exposure and event cannot be overemphasised. Finally, in a sensitivity analysis of the studies with high quality scores included in this metaanalysis, the reduction of breast cancer risk reported was even higher, at 27% (83).…”
Section: Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 88%
“…The significance of case-control studies in defining the causal relationship between exposure and event cannot be overemphasised. Finally, in a sensitivity analysis of the studies with high quality scores included in this metaanalysis, the reduction of breast cancer risk reported was even higher, at 27% (83).…”
Section: Epigallocatechin-3-gallate (Egcg)mentioning
confidence: 88%
“…Previous studies have shown that it can prevent both dental caries and periodontal disease [10][11][12]. In addition to its beneficial effects on various health outcomes, such as all-cause mortality, cardiovascular disease, cancers, non-alcoholic fatty liver disease, metabolic syndrome, diabetes, and other health outcomes [13][14][15][16][17][18][19][20], green tea consumption is also considered to have an effect on oral health. In spite of abundant benefits from the basic sciences, there are relatively fewer clinical studies on the merit of green tea on oral health [21].…”
Section: Introductionmentioning
confidence: 99%
“…Current reports are conflicting in regards to the correlation between breast cancer occurrence and green tea consumption. Some reports have shown an inverse correlation, while other reports have identified no benefit of tea consumption on breast cancer prevention or occurrence [56,57]. However, breast cancer risk has been reported to be considerably lower among Asian women compared to Western populations.…”
Section: Epigallocatechin Regulates Tumor Suppressor Genes By Promotementioning
confidence: 99%